Education in the Era of Technological Disruptions: Analysis of the Role of Innovation in the Learning Process - Suhilmiati, Endhang; Muh. Zuhdy Hamzah; Hariani; Harapin Hafid (PT Inovasi Pratama Internasional, 2025)
This study aims to analyze the forms, experiences, and meanings of learning innovations applied by teachers and educational units in facing the era of technological disruption. Using an exploratory qualitative approach and case study method, this study was conducted at SMP Negeri 1 Banyuwangi, involving teachers, students, and the principal as the main informants. Data collection techniques include in-depth interviews, classroom observations, and documentation analysis. The results of the study indicate that the forms of learning innovation include the use of artificial intelligence (AI), the Learning Management System (LMS) platform, interactive learning videos, and blended learning models. Teachers and students experience significant changes in their roles and learning methods. This innovation is interpreted as a process of adaptation to the demands of the times and is considered capable of increasing the efficiency and quality of learning, although there are still obstacles such as limited access to technology. This study strengthens the relevance of the Diffusion of Innovation, TPACK, and SAMR theories in the context of digital learning and provides implications for the development of contextual and sustainable digital transformation-based education policies.